Regional Trade Union Seminar on prices policy (Organisation of Economic Cooperation and Development Paris, 1972)
This context some countries have taken action which will directly affect prices. General price freezes or more selective controls have been applied or considered.
aia 13/02/2019
Loans
Keywords: Price regulation; Wage-price policy; Pricing